Extracellular vesicles derived from endometrial human mesenchymal stem cells enhance embryo yield and quality in an aged murine model†. Issue 5 (28th December 2018) - Marinaro, Federica; Macías-García, Beatriz; Sánchez-Margallo, Francisco Miguel; Blázquez, Rebeca; Álvarez, Verónica; Matilla, Elvira; Hernández, Nuria; Gómez-Serrano, María; Jorge, Inmaculada; Vázquez, Jesús; González-Fernández, Lauro; Pericuesta, Eva; et al.
Abstract: Advanced age is a risk factor undermining women's fertility. Hence, the optimization of assisted reproduction techniques is an interdisciplinary challenge that requires the improvement of in vitro culture systems. Here, we hypothesize that supplementation of embryo culture medium with extracellular vesicles from endometrial-derived mesenchymal stem cells (EV-endMSCs) may have a positive impact on the embryo competence of aged oocytes. In this work, 24 weeks old B6D2 female mice were used as egg donors and in vitro fertilization assays were performed using males from the same strain (8–12 weeks); the presumptive zygotes were incubated in the presence of 0, 10, 20, 40, or 80 μg/ml of EV-endMSCs. The results from the proteomic analysis of EV-endMSCs and the classification by Reactome pathways allowed us to identify proteins closely related with the fertilization process. Moreover, in our aged murine model, the supplementation of the embryo culture medium with EV-endMSCs improved the developmental competence of the embryos as well as the total blastomere count. Finally, gene expression analysis of murine blastocysts showed significant changes on core genes related to cellular response to oxidative stress, metabolism, placentation, and trophectoderm/inner cell mass formation. In summary, we demonstrate that EV-endMSCs increase the quality of the embryos, and according to proteomic and genomic analysis, presumably by modulating the expression of antioxidant enzymes and promoting pluripotent activity. Therefore, EV-endMSCs could be a valuable tool in human assisted reproduction improving the developmental competence of aged oocytes and increasing the odds of implantation and subsequent delivery. Abstract : The supplementation of embryo culture medium with extracellular vesicles from endometrial-derived mesenchymal stem cells increases the quality of aged embryos.